REMBI: Recommended Metadata for Biological Images—enabling reuse of microscopy data in biology - Sarkans, U; Chiu, W; Collinson, L; Darrow, MC; Ellenberg, J; Grunwald, D; Hériché, J-K; Iudin, A; Martins, GG; Meehan, T; Narayan, K; Patwardhan, A; et al. (Springer Nature, 2021)
Bioimaging data have significant potential for reuse, but unlocking this potential requires systematic archiving of data and metadata in public databases. We propose draft metadata guidelines to begin addressing the needs of diverse communities within light and electron microscopy. We hope this publication and the proposed Recommended Metadata for Biological Images (REMBI) will stimulate discussions about their implementation and future extension.